Preparation process of conductive electrode of large-size graphitization furnace end
By optimizing the connection of the power transmission curve and the flexible graphite ring, the crack problem caused by the unreasonable heating curve in the conductive electrode of the large-scale graphitized furnace head is solved, which improves the yield and density and reduces production costs.
Patent Information
- Application Number
- CN202411420600.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-12
AI Technical Summary
In the industrial production of large-scale graphitized furnace head conductive electrodes, the overall longitudinal crack of the electrode is a common quality problem. The internal stress changes caused by the unreasonable power transmission and heating curve exceed the product expansion limit, causing cracks.
The optimized power transmission curve and specific flexible graphite ring connection method are adopted to control the internal stress and temperature distribution of the electrode to reduce cracks. Specific measures include: multi-stage adjustment of the power transmission curve and the design of flexible graphite rings to ensure uniform current passing through and avoid excessive temperature difference between internal temperature and surface.
It effectively reduces the cracks of the electrodes during graphitization, improves the yield and density of large-scale graphitization furnace head conductive electrodes, and reduces production costs.
Smart Images

Figure CN119219418A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of graphite preparation, and in particular to a process for preparing a large-scale graphitized furnace head conductive electrode. Background Art
[0002] Lengthwise graphitization furnace: a resistance furnace that directly passes current into the furnace to connect the baked products in series, and uses the resistance of the products themselves to convert electrical energy into heat energy to graphitize the products. Its basic principle is to place the baking electrodes horizontally in the furnace, connect them in series along their axis, and then fix them between two conductive electrodes. In order to reduce heat loss, the baking electrodes are covered with insulation materials.
[0003] In the internal heat series graphitization furnace, the heating time, the temperature rise curve and the final graphitization temperature are important factors affecting the final graphitization effect of the baked product and the energy consumption level of the furnace. The overall longitudinal cracking of the electrode is a quality problem often encountered in the internal series graphitization production, and it is also a major problem affecting the production cost of the electrode. One of the main reasons for the overall longitudinal cracking of the electrode is the unreasonable design of the power transmission temperature rise curve, which causes the change of the internal stress of the electrode to exceed the limit stress of the product itself and form longitudinal cracks.
[0004] The series graphitized series column is composed of several baked products connected in series in the longitudinal direction and pressed together. The end face contact part is a key place. During the power-on process, the temperature of the contact part rises due to the large resistance of the end face contact position, which easily causes cracks in the end face contact part; the electrode contact area is too large, resulting in too much current passing through the center of the electrode, and the thermal expansion force inside the product is greater than the surface layer, forming longitudinal cracks. In this regard, when loading the furnace, a flexible graphite gasket of appropriate thickness is embedded in the connection between the ends of the two baked products and pressed tightly, which can reduce the occurrence of such cracks.
[0005] CN201711421602.4 A super-large graphite product and its graphitization method, involving graphite product processing, specifically using an Acheson graphitization furnace, by adjusting the initial furnace core resistance, changing the furnace loading method of super-large graphite products and adjusting the power rise rate of the power transmission curve, so that the graphitized products have good density performance and improve the yield rate. CN201510655607.8 A graphitization method for fine-grained graphite products using an Acheson graphitization furnace, involving the manufacturing and processing field of graphite materials, greatly reducing the generation of graphitization crack waste, improving the yield rate of the graphitization process, reducing the graphitization production cost, and increasing the company's economic benefits. CN201410368599.4 A graphite electrode with a diameter of 348 mm and its production method, using an Acheson graphitization furnace, successfully solved the problem that small-particle powder multi-electrodes are easy to crack during roasting and graphitization heat treatment, and the yield rate is low.
[0006] CN201110182804.4 A 318mm diameter ultra-high power graphite electrode joint and its production method, which solves the problem that coal-based needle coke cannot produce large-scale ultra-high power graphite electrode joints due to poor main physical and chemical indicators, thereby realizing the localization of the main raw materials of ultra-high power graphite electrode joints. CN202011135511.6 A φ700mm ultra-high power graphite electrode preparation process, using domestic Jingyang needle coke, calcined petroleum coke, and graphite as aggregates, and medium-temperature modified coal tar with a softening point of 95-105℃ and a coking value of ≥58% as a binder to manufacture φ700mm ultra-high power graphite electrodes. Summary of the invention
[0007] The purpose of the present invention is to provide a large-scale graphitization furnace head conductive electrode preparation process, the use of this process reduces the large-scale graphitization furnace head conductive electrode cracks in low-cost industrial production; by optimizing the power transmission curve accordingly to ensure the effect and quality of graphitization.
[0008] The present invention adopts the following technical solutions: A large-scale graphitization furnace head conductive electrode preparation process, using a series-connected graphitization furnace for graphitization, The power transmission curve during power transmission is: Starting power 2350~2450kW; In the first stage, the power is increased to 2900-3000kW, which takes 6-6.5 hours; In the second stage, the power is reduced to 2400-2500kW, which takes 3-3.5 hours; In the third stage, the power is increased to 5250-5350kW, which takes 39-41 hours; In the fourth stage, the power is increased to 6550-6650 kW, which takes 6-6.5 hours; In the fifth stage, the power is increased to 12,000 kW, which takes 3.479 to 3.518 hours; In the sixth stage, the power is maintained at 12000 kW for 2 to 2.5 hours.
[0009] As a preferred method, a linear series graphitization furnace is used for graphitization, and the power transmission curves of the first stage, the second stage, the third stage, and the fourth stage are all linear; the power transmission curve of the fifth stage is: Y=Z+154*X+511.75*X*X-32.72*X*X*X Y is the power transmission; X is time, and Z is the power transmission at the end of the fourth stage.
[0010] Preferably, the conductive electrode of the large-sized graphitizing furnace head has a length of 3000-5000 mm and a diameter of 1400-2000 mm.
[0011] As a preferred method, a linear series graphitization furnace is used for graphitization, and the power transmission curve during power transmission is: Starting power 2415kW; In the first stage, the power was increased to 2920-2960 kW, which took 6.3-6.5 hours; In the second stage, the power is reduced to 2430-2470 kW, which takes 3-3.2 hours; In the third stage, the power is increased to 5280-5330 kW, which takes 39.5-40.5 hours; In the fourth stage, the power is increased to 6595kW, which takes 6.3 to 6.5 hours; In the fifth stage, the power was increased to 12,000 kW, which took 3.5 hours. In the sixth stage, the power is maintained at 12000 kW for 2.4 to 2.5 hours.
[0012] In the fifth stage, the power transmission curve is: Y=6595+154*X+511.75*X*X-32.72*X*X*X; Y is the power transmitted; X is time.
[0013] Preferably, the preparation process of conductive electrodes for large-scale graphitizing furnace heads, the graphitization process of the serial graphitizing furnace includes: furnace body preparation, laying of insulation materials, loading of electrode blanks, laying of insulation materials, and power transmission.
[0014] Preferably, the thermal insulation material is composed of 30% to 40% by volume of graphitized metallurgical coke and 60% to 70% by volume of metallurgical coke.
[0015] Preferably, the electrode blank is prepared from the following raw materials in parts by weight: 6 to 10 parts of petroleum coke with a particle size of 6 to 9 mm; 42-49 parts of petroleum coke with a particle size of 1-6 mm; 6 to 10 parts of petroleum coke with a particle size of 0.5 to 1 mm; 34-41 parts of petroleum coke with a particle size of less than 0.5 mm; 17-23 parts of coal tar.
[0016] Preferably, the electrode blank is prepared from the following raw materials in parts by weight: 6 to 10 parts of sponge coke with a particle size of 6 to 9 mm; 42 to 49 parts of shot coke with a particle size of 1 to 6 mm; 6 to 10 parts of shot coke with a particle size of 0.5 to 1 mm; 34-41 parts of petroleum coke with a particle size of less than 0.5 mm, 50% each of sponge coke and shot coke; Softening point 105℃~115℃ Coal tar 17~23 parts.
[0017] Preferably, the electrode blank is made by the following steps: mixing ingredients, kneading, vibration molding, and baking in a baking furnace to obtain the electrode blank.
[0018] Preferably, the end faces of the electrode blanks are connected by a flexible graphite ring, the thickness of the flexible graphite ring is 20 mm to 30 mm, and the ratio of the inner diameter to the outer diameter of the flexible graphite ring is 5 to 7:10.
[0019] Preferably, the flexible graphite ring has a 3-4mm diameter through hole in the 20-30% area of the annular width near the inner edge, and the porosity is 20-30%; the flexible graphite ring has no holes in the 15-20% area of the annular width near the outer edge; and the remaining area of the flexible graphite ring has 1.5-2mm diameter through holes, and the porosity is 10-15%.
[0020] Compared with the prior art, the large-scale graphitized furnace head conductive electrode preparation process of the present invention has the following beneficial effects: The optimized graphitization power supply curve of the present invention is aimed at the industrial production of large-scale graphite electrodes, ensuring that the internal stress and volatile matter are within a controllable range during the graphitization temperature rise process, reducing the internal force generated during the graphitization process and thus reducing cracks, and the temperature distribution is uniform, greatly reducing the occurrence of crack failures.
[0021] The specific graphitization power supply curve of the present invention controls the excessively rapid reaction and release of sulfur and sulfur-carbon compounds during high-temperature heating for electrode blanks with high sulfur content in sponge coke and shot coke, prevents the formation of tiny holes and cracks in the electrode, improves the density and conductivity, and solves the problem of high-yield industrial production of large-scale graphitized furnace head conductive electrodes with high sulfur content.
[0022] The present invention adopts a special flexible graphite gasket to ensure that the current can pass through more of the electrode surface during the power transmission process, thereby avoiding cracks caused by a large temperature difference between the internal temperature and the surface of the electrode during the power transmission process. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 It is a schematic diagram of the power transmission curves in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.
[0024] Figure 2 Schematic diagram of the flexible graphite ring in Example 1, Example 2, and Example 3 of the present invention. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0026] Embodiment 1: A large-scale graphitization furnace head conductive electrode preparation process adopts a serial graphitization furnace for graphitization, including furnace body preparation, laying of insulation material, loading of electrode blanks, laying of insulation material, and power transmission.
[0027] Among them, the power transmission curve during power transmission is: Starting power 2415kW; In the first stage, the power increased linearly to 2938kW, which took 6.5 hours; In the second stage, the power was linearly reduced to 2455kW, which took 3 hours; In the third stage, the power increased linearly to 5306kW, which took 40 hours; In the fourth stage, the power increased linearly to 6595kW, which took 6.5 hours; In the fifth stage, the power is increased to 12,000 kW, which takes 3.5 hours; In the sixth stage, the power is maintained at 12,000 kW for 2.5 hours; In the fifth stage, the power transmission curve is: Y=6595+154*X+511.75*X*X-32.72*X*X*X; Y is the power transmitted; X is the time, ranging from (0 to 3.5).
[0028] The thermal insulation material is composed of 30% to 40% by volume of graphitized metallurgical coke and 60% to 70% by volume of metallurgical coke.
[0029] Among them, the size of the large-sized graphitized furnace head conductive electrode is 4800mm long and 2000mm in diameter.
[0030] The end faces of the electrode blanks are connected by a flexible graphite ring, the thickness of the flexible graphite ring is 25 mm, and the ratio of the inner diameter to the outer diameter of the flexible graphite ring is 5.5:10. Figure 2 As shown, the flexible graphite ring has an annular width of 128 mm in area 3 near the inner edge, with a through hole of 3.4 mm in diameter, and an opening rate of 20-30%; the flexible graphite ring has an annular width of 78 mm in area 1 near the outer edge, without a hole; the remaining area 2 of the flexible graphite ring has through holes of 1.6 mm in diameter, and an opening rate of 10-15%.
[0031] The preparation of electrode blanks includes the following steps: 6 to 10 parts of sponge coke with a particle size of 6 to 9 mm, 42 to 49 parts of shot coke with a particle size of 1 to 6 mm, 6 to 10 parts of shot coke with a particle size of 0.5 to 1 mm, and 34 to 41 parts of petroleum coke with a particle size of less than 0.5 mm, wherein the sponge coke and shot coke each account for 50%; the dry ingredients of the sponge coke and shot coke are mixed; 17 to 23 parts of coal tar are added for kneading; the mixture is vibrated and formed in a vibration molding device and placed in a water pool for cooling; and the mixture is placed in a roasting furnace for roasting.
[0032] Among them, the shot coke is pre-treated by calcining at 1900℃~2200℃ for 5~10 minutes before being crushed; Among them, the softening point of coal tar is 105℃~115℃, the sulfur content is ≤2%, the ash content is ≤0.3%, and the sulfur content is ≤0.3%.
[0033] The blank is preheated to 150°C and placed in a roasting furnace for roasting. A natural gas ring roasting furnace is used. There are 8 furnace chambers in the heating state. The maximum roasting temperature is 1000°C to 1100°C. The roasting is carried out for 768 hours under air-tight conditions. Stage 1: It takes 96 hours, and the temperature rises linearly from 150°C to 230°C; The second stage: It takes 48 hours, and the temperature rises linearly from 230℃ to 276℃; The third stage: It takes 48 hours, and the temperature rises linearly from 276℃ to 324℃; Stage 4: It took 96 hours, and the temperature increased linearly from 324°C to 431°C; Stage 5: It took 192 hours, and the temperature increased linearly from 431°C to 606°C; Stage 6: It took 252 hours, the temperature rose from 606°C to 1078°C, and the temperature rise curve was: Y=1169.365-3.17*(X+480)+0.00416*(X+480)*(X+480); Y is temperature; X is time, ranging from (0 to 252); Stage 7: 732-768 hours, temperature maintained at 1078°C.
[0034] Embodiment 2: A large-scale graphitization furnace head conductive electrode preparation process adopts a linear series graphitization furnace for graphitization, including furnace body preparation, laying of insulation material, loading of electrode blanks, laying of insulation material, and power transmission.
[0035] Among them, the power transmission curve during power transmission is: Starting power 2350kW; In the first stage, the power was increased to 2900kW, which took 6 hours; In the second stage, the power was reduced to 2400kW, which took 3 hours; In the third stage, the power was increased to 5250kW, which took 39 hours; In the fourth stage, the power was increased to 6550kW, which took 6 hours; In the fifth stage, the power was increased to 12,000 kW, which took 3.518 hours; In the sixth stage, the power is maintained at 12000kW for 2 hours; In the fifth stage, the power transmission curve is: Y=6550+154*X+511.75*X*X-32.72*X*X*X; Y is the power transmitted; X is the time, ranging from (0 to 3.518).
[0036] The thermal insulation material is composed of 30% to 40% by volume of graphitized metallurgical coke and 60% to 70% by volume of metallurgical coke.
[0037] Among them, the size of the conductive electrode of the large-sized graphitized furnace head is 3000mm long and 1400mm in diameter.
[0038] The end faces of the electrode blanks are connected by a flexible graphite ring, the thickness of the flexible graphite ring is 20 mm, and the ratio of the inner diameter to the outer diameter of the flexible graphite ring is 5:7. Figure 2 As shown, the 40mm-wide area 3 of the flexible graphite ring near the inner edge is provided with through holes with a diameter of 3mm, and the porosity is 20-30%; the 30mm-wide area 1 of the flexible graphite ring near the outer edge is not provided with holes; the remaining area 2 of the flexible graphite ring is provided with through holes with a diameter of 1.5mm, and the porosity is 10-15%.
[0039] The preparation of electrode blanks includes, by mass: 6 to 10 parts of sponge coke with a particle size of 6 to 9 mm, 42 to 49 parts of shot coke with a particle size of 1 to 6 mm, 6 to 10 parts of shot coke with a particle size of 0.5 to 1 mm, 34 to 41 parts of petroleum coke with a particle size of less than 0.5 mm, with sponge coke and shot coke each accounting for 50%, mixing the sponge coke and shot coke dry materials; adding 17 to 23 parts of coal tar for kneading; vibrating and molding in a vibration molding device and placing in a water pool for cooling; and placing in a roasting furnace for roasting.
[0040] Among them, the shot coke is pre-treated by calcining at 1900℃~2200℃ for 5~10 minutes before being crushed; Among them, the softening point of coal tar is 105℃~115℃, the sulfur content is ≤2%, the ash content is ≤0.3%, and the sulfur content is ≤0.3%.
[0041] Embodiment 3: A large-scale graphitization furnace head conductive electrode preparation process adopts a linear series graphitization furnace for graphitization, including furnace body preparation, laying of insulation material, loading of electrode blanks, laying of insulation material, and power transmission.
[0042] Among them, the power transmission curve during power transmission is: Starting power 2450kW; In the first stage, the power was increased to 3000kW, which took 6.5 hours; In the second stage, the power was reduced to 2500kW, which took 3.5 hours; In the third stage, the power was increased to 5350kW, which took 41 hours; In the fourth stage, the power was increased to 6650kW, which took 6.5 hours; In the fifth stage, the power was increased to 12000kW, which took 3.479 hours. In the sixth stage, the power is maintained at 12,000 kW for 2.5 hours; In the fifth stage, the power transmission curve is: Y=6650+154*X+511.75*X*X-32.72*X*X*X; Y is the power transmitted; X is the time, ranging from (0 to 3.479).
[0043] The thermal insulation material is composed of 30% to 40% by volume of graphitized metallurgical coke and 60% to 70% by volume of metallurgical coke.
[0044] Among them, the size of the large-sized graphitized furnace head conductive electrode is 5000mm long and 2000mm in diameter.
[0045] The end faces of the electrode blanks are connected by a flexible graphite ring, the thickness of the flexible graphite ring is 30 mm, and the ratio of the inner diameter to the outer diameter of the flexible graphite ring is 5:10. Figure 2 As shown, the 150mm-wide area 3 of the flexible graphite ring near the inner edge is provided with through holes with a diameter of 4mm, and the porosity is 20-30%; the 100mm-wide area 1 of the flexible graphite ring near the outer edge is not provided with holes; the remaining area 2 of the flexible graphite ring is provided with through holes with a diameter of 2mm, and the porosity is 10-15%.
[0046] The preparation of electrode blanks includes, by mass: 6 to 10 parts of sponge coke with a particle size of 6 to 9 mm, 42 to 49 parts of shot coke with a particle size of 1 to 6 mm, 6 to 10 parts of shot coke with a particle size of 0.5 to 1 mm, 34 to 41 parts of petroleum coke with a particle size of less than 0.5 mm, with sponge coke and shot coke each accounting for 50%, mixing the sponge coke and shot coke dry materials; adding 17 to 23 parts of coal tar for kneading; vibrating and molding in a vibration molding device and placing in a water pool for cooling; and placing in a roasting furnace for roasting.
[0047] Among them, the shot coke is pre-treated by calcining at 1900℃~2200℃ for 5~10 minutes before being crushed; Among them, the softening point of coal tar is 105℃~115℃, the sulfur content is ≤2%, the ash content is ≤0.3%, and the sulfur content is ≤0.3%.
[0048] Comparative Example 1: The difference from Example 1 is that the power transmission power curve in CN201110182804.4 is: Starting power 3600kW; In the first stage, the power is linearly increased to 5000kW, which takes 4 hours; In the second stage, the power is linearly reduced to 4200kW, which takes 1 hour; In the third stage, the power is linearly increased to 4700kW, which takes 1 hour; In the fourth stage, the power is linearly increased to 5500kW, which takes 1 hour; In the fifth stage, the power is linearly increased to 8500kW, which takes 1 hour; In the sixth stage, the power is linearly increased to 11,000 kW, which takes 1 hour; In the seventh stage, the power is linearly increased to 13,000 kW, which takes 1 hour; In the eighth stage, the power is maintained at 13,000 kW and the duration is 2 hours.
[0049] Comparative Example 2: The difference from Example 1 is that the power transmission curve during power transmission is: Starting power 2415kW; In the first stage, the power was linearly increased to 3000kW, which took 6.5 hours; In the second stage, the power was linearly reduced to 2520kW, which took 3 hours; In the third stage, the power is linearly increased to 6000kW, which takes 40 hours; In the fourth stage, the power increased linearly to 9016kW, which took 6.5 hours; In the fifth stage, the power is linearly increased to 12,000 kW, which takes 3.5 hours; In the sixth stage, the power is maintained at 12000kW for 2.5 hours.
[0050] Comparative Example 3: A large-scale graphitization furnace head conductive electrode preparation process adopts a serial graphitization furnace for graphitization, including furnace body preparation, laying of insulation material, loading of electrode blanks, laying of insulation material, and power transmission.
[0051] Among them, the power transmission curve during power transmission is: Starting power 2415kW; In the first stage, the power increased linearly to 2938kW, which took 6.5 hours; In the second stage, the power was linearly reduced to 2455kW, which took 3 hours; In the third stage, the power increased linearly to 5306kW, which took 40 hours; In the fourth stage, the power increased linearly to 6595kW, which took 6.5 hours; In the fifth stage, the power is increased to 12,000 kW, which takes 3.5 hours; In the sixth stage, the power is maintained at 12,000 kW for 2.5 hours; In the fifth stage, the power transmission curve is: Y=6595+154*X+511.75*X*X-32.72*X*X*X; Y is the power transmitted; X is the time, ranging from (0 to 3.5).
[0052] The thermal insulation material is composed of 30% to 40% by volume of graphitized metallurgical coke and 60% to 70% by volume of metallurgical coke.
[0053] Among them, the size of the large-sized graphitized furnace head conductive electrode is 5000mm long and 2000mm in diameter.
[0054] The end faces of the electrode blanks are connected by flexible graphite rings, the thickness of the flexible graphite rings is 20 mm, and the ratio of the inner diameter to the outer diameter of the flexible graphite rings is 6:10.
[0055] Comparative Example 4: A large-scale graphitization furnace head conductive electrode preparation process, using a serial graphitization furnace for graphitization, including furnace body preparation, laying of insulation material, loading of electrode blanks, laying of insulation material, and power transmission.
[0056] Among them, the power transmission curve during power transmission is: Starting power 2415kW; In the first stage, the power increased linearly to 2938kW, which took 6.5 hours; In the second stage, the power was linearly reduced to 2455kW, which took 3 hours; In the third stage, the power increased linearly to 5306kW, which took 40 hours; In the fourth stage, the power increased linearly to 6595kW, which took 6.5 hours; In the fifth stage, the power is increased to 12,000 kW, which takes 3.5 hours; In the sixth stage, the power is maintained at 12,000 kW for 2.5 hours; In the fifth stage, the power transmission curve is: Y=6595+154*X+511.75*X*X-32.72*X*X*X; Y is the power transmitted; X is the time, ranging from (0 to 3.5).
[0057] The thermal insulation material is composed of 30% to 40% by volume of graphitized metallurgical coke and 60% to 70% by volume of metallurgical coke.
[0058] Among them, the size of the large-sized graphitized furnace head conductive electrode is 5000mm long and 2000mm in diameter.
[0059] The end faces of the electrode blanks are connected by a flexible graphite ring, the thickness of the flexible graphite ring is 25 mm, and the ratio of the inner diameter to the outer diameter of the flexible graphite ring is 5.5: 10. The surface of the flexible graphite ring is provided with a through hole with an aperture of 3.4 mm, and the opening rate is 20-30%.
[0060] Table 1: Comparison of indicators between Examples 1-3 and Comparative Examples 1-4
[0061] As can be seen from Table 1, in Examples 1 to 3, the electrode blanks used were the same, and the power transmission curves were adjusted within the range respectively; the main indicators of the obtained graphitized furnace head conductive electrodes were relatively close.
[0062] Comparative Example 1 uses a 12-hour power supply curve, but this power supply curve not only fails to effectively complete graphitization, but also has an extremely high crack failure rate. This is because there is no optimized power supply curve determined for different electrode blank formulations and sizes.
[0063] Comparative Example 2 adopts a 62-hour power transmission curve similar to that of Example 1, but the power transmission curve does not achieve optimal control in the range of 1400-1800°C. In this link, elements such as oxygen, nitrogen, and sulfur bound to the carbon microcrystalline structure escape, especially the increased escape of gaseous sulfides, resulting in more micropores and cracks, which affects the main indicators of the conductive electrode of the graphitized furnace head.
[0064] Comparative Example 3 uses ordinary flexible graphite rings for connection, while Comparative Example 4 uses flexible graphite rings with a simple through hole of 3.4 mm in diameter for connection, and the rest of the steps are the same as those of Example 1. Compared with the flexible graphite rings with specific stage-by-stage perforations for guiding current in Example 1 of the present invention; Comparative Example 3 and Comparative Example 4 have slightly poor ability to guide more current to the electrode surface, so the crack rate at the end contact part is slightly higher, which has an impact on the conductive electrode of the graphitized furnace head.
Claims
1. A large-scale graphitized furnace head conductive electrode preparation process, characterized in that: The graphitization is carried out using a serial graphitization furnace, and the power transmission curve during power transmission is: Starting power 2350~2450kW; In the first stage, the power is increased to 2900-3000kW, which takes 6-6.5 hours; In the second stage, the power is reduced to 2400-2500kW, which takes 3-3.5 hours; In the third stage, the power is increased to 5250-5350kW, which takes 39-41 hours; In the fourth stage, the power is increased to 6550-6650 kW, which takes 6-6.5 hours; In the fifth stage, the power is increased to 12,000 kW, which takes 3.479 to 3.518 hours; In the sixth stage, the power is maintained at 12000 kW for 2 to 2.5 hours.
2. The process for preparing a large-scale graphitized furnace head conductive electrode according to claim 1, characterized in that: A linear series graphitization furnace is used for graphitization. The power transmission curves of the first, second, third and fourth stages are all linear; the power transmission curve of the fifth stage is: Y=Z+154*X+511.75*X*X-32.72*X*X*X Y is the power transmission; X is time, and Z is the power transmission at the end of the fourth stage.
3. The process for preparing a large-scale graphitized furnace head conductive electrode according to claim 2, characterized in that: The size of the conductive electrode of the large-scale graphitized furnace head is 3000-5000mm in length and 1400-2000mm in diameter.
4. The process for preparing a large-scale graphitized furnace head conductive electrode according to claim 3 is characterized in that: The graphitization is carried out using a linear series graphitization furnace, and the power transmission curve during power transmission is: Starting power 2415kW; In the first stage, the power was increased to 2920-2960 kW, which took 6.3-6.5 hours; In the second stage, the power is reduced to 2430-2470 kW, which takes 3-3.2 hours; In the third stage, the power is increased to 5280-5330 kW, which takes 39.5-40.5 hours; In the fourth stage, the power is increased to 6595kW, which takes 6.3 to 6.5 hours; In the fifth stage, the power is increased to 12,000 kW, which takes 3.5 hours; In the sixth stage, the power is maintained at 12000kW for 2.4 to 2.5 hours; In the fifth stage, the power transmission curve is: Y=6595+154*X+511.75*X*X-32.72*X*X*X; Y is the power transmitted; X is time.
5. The process for preparing a large-scale graphitized furnace head conductive electrode according to claim 1, characterized in that include: Prepare the furnace body, lay insulation material, load electrode blanks, cover with insulation material, and supply power.
6. The process for preparing a large-scale graphitized furnace head conductive electrode according to claim 5, characterized in that: The thermal insulation material consists of 30% to 40% of graphitized metallurgical coke and 60% to 70% of metallurgical coke in volume percentage.
7. The process for preparing a large-scale graphitized furnace head conductive electrode according to claim 5, characterized in that: The electrode blank is prepared from the following raw materials in parts by weight: 6 to 10 parts of petroleum coke with a particle size of 6 to 9 mm; 42-49 parts of petroleum coke with a particle size of 1-6 mm; 6 to 10 parts of petroleum coke with a particle size of 0.5 to 1 mm; 34-41 parts of petroleum coke with a particle size of less than 0.5 mm; 17-23 parts of coal tar.
8. The process for preparing a large-scale graphitized furnace head conductive electrode according to claim 7, characterized in that: The electrode blank is prepared by the following steps: mixing ingredients, kneading, vibration molding, and baking in a baking furnace to obtain the electrode blank.
9. The process for preparing a large-scale graphitized furnace head conductive electrode according to claim 5, characterized in that: The end faces of the electrode blanks are connected by a flexible graphite ring, the thickness of the flexible graphite ring is 20 mm to 30 mm, and the ratio of the inner diameter to the outer diameter of the flexible graphite ring is 5 to 7:
10.
10. The process for preparing a large-scale graphitized furnace head conductive electrode according to claim 9, characterized in that: The flexible graphite ring is provided with a through hole with a diameter of 3 to 4 mm in an area of 20 to 30% of the annular width near the inner edge, and the opening rate is 20 to 30%; The flexible graphite ring has no holes in the area of 15-20% of the annular width near the outer edge; The remaining area of the flexible graphite ring is distributed with through holes with a diameter of 1.5 to 2 mm, and the opening rate is 10 to 15%.
Citation Information
Patent Citations
Graphitizing method and graphitizing device of graphite product
CN108083269A
Double-column internal cascading type graphitization production method for ultrahigh-power graphite electrode
CN108218426A
Electrode graphitization power transmission curve optimization method
CN116951982A
Low-cost high-density graphitized carbon block and preparation process thereof
CN118619675A
Low-density flexible graphite annulus
CN201141006Y
Cited By
A method for heating a graphitized cathode carbon block
CN122789731A